Decoloniality in making science in a science club (Research, Society and Development, 2020)
This text discusses decoloniality in a science club based on the analysis of the questionnaire applied to the monitors, was verified how they classify the science that is made in this place, the use of materials and the agreement on the use of these materials in experiments scientific research carried out in this educational place. The qualitative approach methodology aims to analyze the content obtained in the questionnaire with monitors and diagnose whether decoloniality is present in doing science through the Investigative Teaching Sequence - ITS. The text presents a discussion about the concepts of decoloniality in educational practices and in making science, doing science through investigative teaching in the science club. The results indicate that the scientific initiation activities carried out in the club differ from doing science, based on the Eurocentric model. And so, it is concluded that the study proved that there is decoloniality present in ITS in the science club.